The French Experience in Algeria The Character of the Fighting and the Political Consequences 1954-1962 - McNulty, Connor (Temporalidades, 2009)
The intent of the paper is to provide a brief overview of the Algerian War and the collapse of the French position. This paper looks from a military and a social viewpoint, and argues that the French colonization of Algeria was based on the notion that Algeria was more than merely a colony and instead was culturally integral to France. The Second World War faced the French with such atrocity that the continental citizens became more mindful of individual liberties and atrocities committed during war, while the French military’s loss of Indochina in 1954 conveyed the lesson that increased brutality was needed to win a counterinsurgency campaign. The French military applied the lessons of Indochina to Algeria and the clash of values almost caused a civil war. De Gaulle took over the Parisian government and over the next few years he suppressed the military and abandoned Algeria, and in the process forced the French to redefine themselves as intolerant of torture and culturally separate from Algeria.